The portfolio : an architecture student's handbook - Marjanović, Igor.; Rüedi, Katerina; Lokko, Lesley Naa Norle (Amsterdam ; Oxford : Architectural, 2003)
The portfolio is the single most important part of every architectural student's education. This book proides a complete guide to preparing, compiling and presenting this crucial element of the architecture course. The experienced author team gives practical advice for the creation of the portfolio covering issues of size, storage, layout and order. They go on to guide the student through the various forms a portfolio can take: the Electronic Portfolio, the Academic Portfolio and the Professional Portfolio suggesting different approaches and different media to use in order to create the strong.
Introduction : why make a portfolio? -- Getting started -- Design cultures -- Academic portfolio -- Professional portfolio -- Preparing the portfolio of work -- The folio container -- Making the traditional portfolio -- Making the digital portfolio -- Afterwards : ways of sending your work.
Includes index.
Print version record.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Architecture portfolios; Portfolios d'architecture.; ARCHITECTURE -- Reference; ARCHITECTURE -- Professional Practice; ARCHITECTURE -- Adaptive Reuse & Renovation; ARCHITECTURE -- Buildings -- General; Architecture portfolios